Scanning Optical Fiber Probes for Leak Detection with Robotic Manipulators - Viana, William Emanuel Silva Santos; Santana, Igor Rocha; Silva, Valéria Loureiro Da; Silva, Lucas Cruz Da (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2023: Anais do XV Simpósio Brasileiro de Robótica e XX Simpósio Latino Americano de Robótica, 2023)
The identification of compounds in aqueous solutions through spectroscopic techniques is well known in the literature. In difficult-to-access environments such as in offshore subsea installations, it is necessary to use small sized instruments coupled to robotic manipulators. In this work, it was demonstrated that the scanning of spectroscopic probes can be used for the detection and localization of fluid leaks. For this purpose, two absorption probes with visible and infrared operations, were coupled to a robotic manipulator that scanned the probes along a simulated leak in a pipe. To facilitate visualization and validation of the technique, a colored automotive coolant, which has a similar composition to offshore hydraulic fluids, was used.